EP144/#481 Sentinel lymph node mapping and dissection using methylene blue: the danang oncology hospital experience of the first 31 cases. (4th December 2022) - Phan, Ngoc; Duong, Trinh; Tran, Quynh; Tran, Quy; Ng, Joseph; Le, Linda Van; Dinh, Tri; Lim, Peter
Abstract : Objectives: Endometrial cancer is the most commonly diagnosed gynecological malignancy in Vietnam, after breast cancer. The primary treatment is based on surgical and pathologic staging including hysterectomy, bilateral salpingo-oophorectomy and pelvic lymphadenectomy. Sentinel lymph node (SLN) mapping for endometrial cancer (EC) is a contemporary technique that could provide benefits over traditional lymphadenectomy. The aim of this study was to describe the results of sentinel node biopsy, and analyze the factors that affect sentinel lymph node mapping. Methods: We collected data from the first 31 cases of patients with endometrial cancer who underwent sentinel lymph nodes by using methylene blue from September 2019 to September 2021. We reported the detection rate and the accuracy of the SLN biopsy. Results: The overall detection rate of sentinel lymph node mapping of at least one site was included in 31 patients was 54.8%, bilateral sentinel node detection rate was 19.3%. The sensitivity and the specificity of the sentinel lymph node was 100%. The detection rate of sentinel lymph node in the first 20 cases was 40% and was 82% in the last 11 cases. Adoption of the SLN technique spared 34.1% hemi pelvic LND from a full lymphadenectomy. Conclusions: Sentinel lymph node sampling by using methylene blue is feasible and accurately predicts lymph node status in patients with endometrial cancer in low resource settings. There is a learning curve to the technique. SLN mapping was more successful after we have done 20 cases.